Uma investigação acerca dos saberes matemáticos na formação de normalistas em Sergipe - Santos, Valdecí Josefa de Jesus (2015)
This paper introduce the results about a study that sought to analyze how mathematical knowledge were organized (Arithmetica, Algebra, Geometry and Design) the Normal course of the Rui Barbosa Educational Institute (IERB) in the State of Sergipe, from the published legislation of 1890 years to 30 years of the 20th century. Therefore, the specific objectives they were drawn: map research carried out the theme on the subject study, starting from the productions in Sergipe, in GHEMAT and Brazil; identify the continuities and the changes in the organization of mathematical knowledge present in the official documents published between the period 1890 to 1930 and identify the type or the method of education prepared to mathematical knowledge for the formation of the primary teachers. The research refers to a qualitative study, of historical in nature and documentary. Valente (2013), Chartier (1990, 2002), Chervel (1990), Le Goff (2003), among other theorists, served as guidance and define base for methodological paths and interpretation of the sources and facts. As main sources were considered official determinations (regulations, laws and teaching programs) specific for the Normal Course after the Proclamation of the Republic. The Public File collections of Sergipe, Public Library Epifânio Dórea, the Official Gazette of Sergipe and the file of Rui Barbosa Educational Institute were prime places for data collection. On examination of the sources were identified math records in the formation of the primary teachers from the beginning of the organization of the course. The mathematics were directed to teaching subject of arithmetica, algebra, geometry and design, but the arithmetic knowledge It has a prominent position, as much as a requirement for admission in the course, as subject recommended in all documents analyzed.